2022
DOI: 10.3390/nano12101637
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochromic Ag-Decorated WO3−x Film with Adjustable Defect States for Electrochemical Surface-Enhanced Raman Spectroscopy

Abstract: Electrochemical surface-enhanced Raman scattering (EC-SERS) spectroscopy is an ultrasensitive spectro-electrochemistry technique that provides mechanistic and dynamic information on electrochemical interfaces at the molecular level. However, the plasmon-mediated photocatalysis hinders the intrinsic electrochemical behavior of molecules at electrochemical interfaces. This work aimed to develop a facile method for constructing a reliable EC-SERS substrate that can be used to study the molecular dynamics at elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Recombination processes usually occur at the trap states of the semiconductor, such as interstitial atoms, vacancies, and grain boundaries [29] . Moreover, the trap states in semiconductor materials can act as electron donors or electron acceptors [30] . Therefore, recombination involving traps which is one of the most important mechanisms in semiconductors, had been extensively studied [29] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombination processes usually occur at the trap states of the semiconductor, such as interstitial atoms, vacancies, and grain boundaries [29] . Moreover, the trap states in semiconductor materials can act as electron donors or electron acceptors [30] . Therefore, recombination involving traps which is one of the most important mechanisms in semiconductors, had been extensively studied [29] .…”
Section: Introductionmentioning
confidence: 99%
“…[29] Moreover, the trap states in semiconductor materials can act as electron donors or electron acceptors. [30] Therefore, recombination involving traps which is one of the most important mechanisms in semiconductors, had been extensively studied. [29] Jung et al studied the photoluminescence (PL) spectra of anatase TiO 2 nanoparticles after calcination at different temperatures and found that PL intensity increased with the increase of calcination temperature, which was owing to the reduction of trap states.…”
Section: Introductionmentioning
confidence: 99%